2022
DOI: 10.1186/s12912-022-00990-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and perceived barriers of nurses working in intensive care unit on pain management of critically ill patients: a cross-sectional study

Abstract: Background Pain is a major obstacle and one of the main reasons people seek medical attention and is a frequent stressor for many clients in the intensive care unit (ICU). However, clients should not be left complaining, especially when solutions are available; each patient has the right to assess and manage their pain in the best way possible. Therefore, the objective of this study was to analyze nurses' knowledge, attitudes, and practice (KAPs) regarding pain management in Palestinian ICU set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Their knowledge and clinical skills can directly affect the patient outcomes. Several previous studies have applied questionnaire surveys to investigate the KAP of nurses in different medical areas (Andegiorgish et al, 2018; Sweity et al, 2022; Wen et al, 2020). In the present study, we used a self‐designed questionnaire to study the KAP of ICU nurses on ASF.…”
Section: Discussionmentioning
confidence: 99%
“…Their knowledge and clinical skills can directly affect the patient outcomes. Several previous studies have applied questionnaire surveys to investigate the KAP of nurses in different medical areas (Andegiorgish et al, 2018; Sweity et al, 2022; Wen et al, 2020). In the present study, we used a self‐designed questionnaire to study the KAP of ICU nurses on ASF.…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of the tool based on the knowledge of NICU nurses on pain assessment among neonates was used. Permission from the original author [27] was obtained.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Given that pain is a significant problem among critically ill adult patients, nurses play a crucial role in its management. However, previous studies found that nurses had insufficient knowledge about pain assessment and management [10,11]. This lack of knowledge was related to nurses' heavy workload, lack of education regarding pain assessment tools, poor documentation and communication of pain assessment priorities [10], and negative attitudes toward pain management [12].…”
Section: Introductionmentioning
confidence: 99%